185k views
3 votes
Solve V= LWH for L

User Nataki
by
4.7k points

1 Answer

3 votes

Answer:


L\text{ = }(V)/(WH)

Step-by-step explanation:

Here, we want to solve the given equation for L

What that means is that we want to make L the formula subject. Hence, we are to simply isolate L on one side of the equation

To do this, we have to divide both sides by the values attached to L:


\begin{gathered} (V)/(WH)\text{ = }(LWH)/(WH) \\ \\ L\text{ = }(V)/(WH) \end{gathered}

User Abinitio
by
4.8k points